Ser cientista: tensões entre gênero e ciência - Pereira, Juliana Cardoso (2011)
This dissertation aims to investigate how the process of gendering of science is being produced at the Institute of Chemistry and Earth Sciences (IQG), Federal University of Pelotas (Pelotas University), Rio Grande do Sul, Brazil. For this, I go around three basic questions: the first shows how it has given the process of deconstruction of the main pillars of modern science positivists held by feminist and gender studies; the second question is based on an analysis of the conception of science and scientist present in the speech of professors-researchers of the Institute and, finally it discusses how the speeches are being made about making science on this place. In this course explored the connection between the invention of modern science and gender studies, highlighting the ways in which it has been giving the gendered production of science.In this sense, it is important to understand what mechanisms, discourses and power relations which are embedded in the process.It presents a conceptual framework in which lists questions regarding the adoption of the concept of gender in this study, considerations about the construction of science and, later on an analysis of how these two areas - gender and science have been crossed themselves. I bring also some works that were produced recently by researchers about the theme, and that reinforce the importance of this issue, both for gender studies, as for science. In the discourse of the scientists interviewed perceives the absence of questions regarding the great myths of positivist science, such as universality, neutrality and objectivity. The presence of women in science can be viewed as a migration from private to public. However, the way it comes hurrying, at least in the discourse of the interviewees, follows a male pattern, to be it to realize the scientific practice, is having to adapt to such standards. And even when sometimes the speeches of these researchers are made any question or protest against male prerogatives, they end up adopting them and defending what is traditionally regarded as science.